Initial feeding behaviour, eye structure and effect of colours on prey capture rates of Betta splendens larvae - do Nascimento, Nivaldo Ferreira [UNESP]; Valentin, Fernanda Nogueira [UNESP]; Pereira-Santos, Matheus [UNESP]; Chavarro, Sheryll Yohana Corchuello [UNESP]; Manzini, Breno [UNESP]; Paes, Maria do Carmo Faria [UNESP]; Faustino, Francine [UNESP]; da Silva, Regiane Cristina [UNESP]; Nakaghi, Laura Satiko Okada [UNESP] (Science Alert, 2015)
Basic studies on early morphology and behaviour are necessary to support applied research on larval rearing. Thus, the aim of this study was to analyze the initial feeding behaviour, eye structure and the influence of different background colours (red, blue and clear) on prey capture rates (Artemia sp.) of Betta splendens larvae. The retina was formed by 90 h post-fertilization and consisted of seven layers. The feeding behaviour of the larvae changed with ocular development and thus, prey were captured more efficiently with time. No significant difference (p>0.05) was observed between the different background colours on prey capture rates under the experimental conditions tested (10 min of exposure). In conclusion, B. splendens larvae displayed a typical feeding behaviour, which changed with larval development and was dependent on visual ontogeny. Even though the different background colours did not significantly affect feeding behaviour, our findings provide important insights for future studies on this field.
Keywords: Aquaculture; Microscopy; Morphology; Ornamental fish